2004
DOI: 10.1002/jlcr.806
|View full text |Cite
|
Sign up to set email alerts
|

A convenient synthesis of 14C‐labelled resveratrol

Abstract: Resveratrol (trans‐3,4′,5‐trihydroxystilbene) is a naturally occurring phytoalexin and polyphenol existing in grapes and various plants. It shows remarkable beneficial bioactivities in the prevention of cancer, inflammation and platelet aggregation, etc. This paper reports the synthesis of [β‐14C]‐trans‐resveratrol using 14C‐formic acid (exchanged with sodium 14C‐formate) and 3,5‐dihydroxybenzoic acid as the starting materials. [14C‐formyl]‐4‐methoxybenzaldehyde and diethyl 3,5‐dimethoxy benzylphosphonate reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The resulting N-methylformanilide 123 was submitted to a Bouveault reaction, to give [ 14 C]-panisaldehyde 124 [82]. The resulting N-methylformanilide 123 was submitted to a Bouveault reaction, to give [ 14 C]-panisaldehyde 124 [82].…”
Section: C-labelling Of Resveratrolmentioning
confidence: 99%
“…The resulting N-methylformanilide 123 was submitted to a Bouveault reaction, to give [ 14 C]-panisaldehyde 124 [82]. The resulting N-methylformanilide 123 was submitted to a Bouveault reaction, to give [ 14 C]-panisaldehyde 124 [82].…”
Section: C-labelling Of Resveratrolmentioning
confidence: 99%
“…The requirement of separating catalysts from products complicates the synthesis process. In addition, Wang and Choi et al , reported the N-formylation of amines using formic acid in the absence of catalyst. However, the reaction required the use of stoichiometric dicyclohexylcarbodiimide as dehydrant, and a restricted substrate scope was acquired.…”
mentioning
confidence: 99%
“…Based on the results of controlled experiments and previous research, a possible reaction mechanism has been proposed (Scheme ). Initially, the lone pair on the N atoms of aniline attacks the activated C atom of HCOOH, producing formate, which then dehydrates to yield the corresponding formamide.…”
mentioning
confidence: 99%